Planejamento Estratégico: uma análise de uma Instituição pública do Amazonas - Ueki, Alice Harumi Gushima (BRASIL, 2024)
The present study aims to identify the importance of strategic planning in public administration, with the locus of study being a public institution in the state of Amazonas. In this context, the research took place due to the relevance of studying the transition from the bureaucratic model to the managerial model, as well as the process of implementing strategic planning in the Institution. To this end, methodologically, an interview was carried out with employees and secondary data was collected, using the transparency portal. The article is divided into five chapters, being introductory, methodological, theoretical framework, analysis, discussions, and final considerations. In the latter, the result is that the institution has been showing signs of applying strategic planning tools as recommended by contingency theory.